Kajian Resistensi Sosial Pengguna Media Sosial X Dalam Tagar #Netizenselalubenar Melalui Analisis Jaringan Komunikasi - Tripalupi, Merry Fridha; Aini, Hanifah Nur; Ayodya, Beta Puspitaning (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2024)
The anecdote that netizens are always right is often used to describe internet users who can comment anything on posts from other people’s accounts. This is sad because it means there are no restrictions on what netizens can and cannot comment on. This phenomenon raises pros and cons, resulting in resistance in netizens who disagree with the concept. This study aims to reveal how audiences respond to #Netizenselalubenar and the resistance that arises on social X. This research uses Computer- Mediated Communication theory and Social network theory. This research provides an overview of the important role of hashtags in exchanging information and forming public opinion. It shows how resistance arises as a response to opinion domination on social media. This research is expected to be a reference for further network analysis research. Moreover, it illustrates the power of netizens’ digital activities in influencing public opinion. The research method used is communication network analysis, which is included in quantitative research with a descriptive approach. Data was taken from tweets on social media X that had activity on #Netizenselalubenar. The main findings include a centralized communication network with several dominant accounts, especially the @0 account. Hashtags disseminate information and shape public opinion regarding the ‘netizens are always right’ phenomenon. Resistance from the audience emerged in response to the dominance of opinion on the hashtag and formed an online community to counter the dominance of the hashtag.